Peran Mahasiswa KKN Pendidikan Biologi dalam Membantu Kegiatan Proses Belajar Mengajar di SMPN 1 Mappakasunggu - Nur Hikmah; Adel Adinda Sari; Dian Safitri; Balak Daeng (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to describe the role of Biology Education Community Service Program students in improving the quality of biology learning at SMPN 1 Mappakasunggu. This study used a descriptive qualitative approach with data collection techniques in the form of observation, interviews, and documentation. The results showed that the Community Service Program students played an active role in various aspects, from lesson planning, implementation of teaching and learning activities, to evaluation of learning outcomes. In addition, the Community Service Program students were also involved in mentoring simple practicums that helped students understand biology concepts more practically. They also contributed to the development of innovative learning media that facilitated students' understanding of the material. The presence of Community Service Program students at the school had a significant positive impact on improving students' conceptual understanding, motivation, and learning activity. Students showed higher enthusiasm in participating in biology learning and experienced improvements in their learning outcomes. Thus, the Community Service Program teaching program is a tangible form of student contribution in supporting the improvement of education quality, especially biology learning in schools with limited resources. This program also provides valuable experience for students to be directly involved in the world of education and have a positive impact on society.